An algorithm measuring the charisma of Greek journalists - Kaimaki , Valia; Ampeliotis, Dimitris; Sgora , Aggeliki; Konidaris , Agisilaos; Polykalas, Spyros (The Greek Review of Social Research, 2024)
X, formerly, Twitter is considered a valuable tool for journalists for real-time interaction with their followers. Especially, in the case of political journalists, the degree of their influence and persuasion is of great importance. In this paper, we deal with identifying the journalists’ political charisma. More specifically we propose an algorithm based on the Analytic Hierarchy Process method to measure the political charisma of the journalists. Numerical results in two different use-case scenarios showed that the proposed algorithm could successfully determine charisma in that it tweaks influence towards a more specific political direction.